Contemporary Chinese dietary pattern: Where are the hidden risks? - Xiang, Hong; Tao, Xufeng; Guan, Xi; Yin, Tianyi; Li, Junchen; Dong, Deshi; Shang, Dong (Frontiers in Nutrition, 2022)
Background: With rapid improvement of economy and lifestyle, dietary risk-related diseases have been a public health problem worldwide. However, the health effects of dietary risks over time have not been fully clarified in China. Here, we explored the temporal trends in the death burden of unhealthy dietary habits in China and benchmark dietary risk challenges in China to G20 member states. Method: Sex-age-specific burden due to dietary risk in China were extracted from the Global Burden of Disease (GBD) Study 2019, including annual numbers and age-standardized rates (ASRs) of death and disability-adjusted life years (DALYs), and summary exposure value (SEV), during 1990-2019. The variation trend of ASRs was evaluated by estimated annual percentage changes (EAPCs). Result: Between 1990 and 2019, the number of dietary risk-based death and DALYs were increased significantly in China with an overall downward trend of ASDR and ASR-DALYs. Ischemic heart disease was the first cause of death from diet, followed by stroke and colon and rectum cancer. Chinese male was at greater risk than female for death and DALY from diet-related causes. Further analysis showed that diet high in sodium has always been the “No.1 killer” that threatens the health of Chinese residents. The death burden of dietary risks demonstrated an increasing trend with age, and a peak was reached in the people over 75 years. Compared with other countries that are members of G20, Japan and South Korea have the most similar dietary patterns to China with a characteristic of high sodium intake. Notably, decreased whole grains intake, as the primary dietary risk attributable to death and DALYs burden in the United States and European countries, had already ranked 2nd in China. Conclusion: China's dietary burden cannot be ignored. Chinese residents should pay more attention to the collocation of dietary nutrients, especially male and 75+ years (old aged). Targeted dietary adjustments can significantly reduce deaths and DALYs.